Kepimpinan transformasi, etika kerja islam, tingkah laku kerja inovatif di sektor awam: pemerkasaan psikologi sebagai pengantara - Surya, Rina Darma (2019)
This study investigated the relationship between transformational leadership and innovative work behavior in the context of the public sector of the Acheh government in Indonesia. It also examined the moderating effect of Islamic work ethics and the mediating effect of psychological empowerment on the relationship between transformational leadership and innovative work behavior. The study was motivated by the inconsistent findings in the literature on the relationship between transformational leadership and innovative work behavior. These inconsistencies led to a new stream of research that indicated the importance of examining the effect of potential moderating variables that could clarify such a relationship. For this purpose, the study took different theories into consideration including the transformational leadership theory, the contingency theory and the cognitive model of empowerment in order to map and position the potential relationships between the variables within the conceptual framework. A total of 281 questionnaires were sent directly to the middle managers of the government of Acheh, Indonesia, through research assistants that had agreed to participate in this study for data collection. However, only 244 questionnaires were returned and only 225 were deemed usable for actual data analysis using PLS-SEM, representing a response rate of 80 %. The direct and indirect relationships between the variables were analyzed using the structural equation model analysis. The findings showed that transformational leadership positively and significantly predicted innovative work behaviors. Meanwhile, Islamic work ethics did not moderate the relationship between transformational leadership and innovative work behavior. Furthermore, the result of the mediation test showed that psychological empowerment mediated the relationship between transformation leadership and innovative work behavior. Implications of the findings, potential limitations and directions for future research are discussed.